Case Study on Public Service Responsibility Implementation in Surabaya via the Broadband Learning Centre Programme - Riduan, Akhmad; Rachmanto, Tito; Brumadyadisty, Garry; Sufa, Siska Armawati; Arfani, M. (IJBLE Scientific Publications Community Inc., 2024)
This study explores the Broadband Learning Centre (BLC) Programme in Surabaya, Indonesia, a municipal initiative to promote digital inclusion and technology access. Through a case study approach, it examines BLC’s strategies to bridge the digital divide, enhance digital literacy, and serve underserved groups, aligning with public service objectives. The research assesses BLC’s effectiveness, explores the challenges in managing and sustaining such initiatives, and addresses a gap in literature on targeted digital inclusion efforts in urban governance. The findings aim to provide insights into the operational model, challenges, and social impact of the BLC Programme, offering implications for similar initiatives seeking to integrate public service responsibilities and advance digital equity in other urban settings.